Effectiveness of Face-to-Face Applied Training in Improving Basic Life Support Knowledge and Skills of Distance-Educated Medical Students - Celik, Fatma; Dagli, Recai; Lale, Hatice Nur; Aksu, Ahmet; Altuntas, Gulsum; Altun, Aysun Yildiz; Demirel, Ismail (Anestezi Dergisi, 2025)
Objective: Basic Life Support (BLS) training is an indispensable element of medical education. Today, in addition to classical face-to-face education, online education has also begun to be used in many areas of medical education. Due to the earthquake disaster in our country, medical faculty students received BLS training only online. The primary aim of this study is to investigate how medical students who received online BLS training improve their knowledge and skills with face-to-face practical BLS training. Our secondary objective is to evaluate the adequacy of BLS knowledge and skills of students who have received distance education. Methods: In this prospective cross-sectional study, a questionnaire containing 14 questions was administered to the medical students who received online BLS training before and three weeks after face-to-face training. Basic life support skill levels were evaluated by two observers, both before and after the training, using training mannequins with continuous visual and auditory feedback. Results: Two hundred-eleven students participated in the study, but the data of 185 students who met the participation criteria were analyzed. After face-to-face training, BLS knowledge levels and performances increased significantly (p<0.001). After the training, compared to before, the decision-making time for cardiopulmonary resuscitation was shortened from 45 seconds to 32 seconds in 97.8% of the students (n=181) (p<0.001). Conclusion: Online education alone has been inadequate in acquiring BLS knowledge and skills. Face-to-face training with a manikin significantly improves students’ information and skill levels. © 2025 Anestezi Dergisi. All rights reserved.
Uzaktan Eğitim Alan Tıp Öğrencilerinin Temel Yaşam Desteği Bilgi ve Becerilerinin Geliştirilmesinde Yüz Yüze Uygulamalı Eğitimin Etkinliği
Keywords: Basic life support; cardiopulmonary resuscitation; medical education